Diagnostic ability of oral rinse active matrix metalloproteinase-8 point-of-care immunotest in Crohn’s disease patients with periodontitis - Kullström, Adrian (My University, 2019)
We hypothesized that the diagnostic accuracy of point-of-care application is weakened in individuals with disrupted immune response. This cross-sectional study aimed to analyze the performance of commercially available oral rinse active matrix metalloproteinase-8 (aMMP-8) point-of-care (PoC) immunotest in people with and without Crohn’s disease. The study population consisted of 47 Crohn’s disease patients, while 41 generally healthy age- and gender-matched individuals served as their controls. From all participants, oral rinse samplings were collected and analyzed by aMMP-8 PoC immunotest according to the manufacturer’s instructions, and their clinical oral status were recorded. The accuracy of the immunotest to diagnose periodontitis was high in systemically healthy controls with test sensitivity of 90.9% and specificity of 80.0%, whereas the corresponding values in the Crohn’s disease group were 60.0% and 75.0%. In both groups, diagnosis of periodontitis associated significantly with the immunotest results, but the odds ratio was over tenfold in controls (odds ratio 54.3 (95% confidence interval: 3.09-953), P=0.006) in comparison to the Crohn’s disease group (odds ratio 5.22 (95% confidence interval: 1.26-21.6), P=0.022). The diagnostic accuracy of aMMP-8 PoC immunotest seems to be reduced in individuals with suppressed immune responses like in Crohn’s disease.